2016
DOI: 10.1080/00016357.2016.1236986
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral calcifying cystic odontogenic tumour and peripheral dentinogenic ghost cell tumour: an updated systematic review of 117 cases reported in the literature

Abstract: Peripheral CCOTs/DGCTs are rare lesions. Most of the lesions were treated by simple excision with or without curettage of the underlying bone. As the recurrence rate is very low, a conservative approach seems to be enough for the great majority of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 57 publications
2
45
0
1
Order By: Relevance
“…() provided an excellent review of 45 cases of PCOC published in the English literature and found that patients were most affected in their 60 s, 70 s and 80 s. Individuals in their 20 s were also significantly affected. This was the same age distribution observed by Brazilian researchers in 2016 (Chrcanovic & Gomez, ). Most individuals complain of painless swelling (Buchner et al., ; Resende, Brito, Souza, Gomez, & Mesquita, ), and the clinical appearance of these lesions was variously described as sessile, nodular, smooth‐surfaced, firm, of soft consistency or as a fibrous mass (Buchner et al., ; de Lima, Kitakawa, Almeida, Brandão, & Anbinder, ; Resende et al., ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…() provided an excellent review of 45 cases of PCOC published in the English literature and found that patients were most affected in their 60 s, 70 s and 80 s. Individuals in their 20 s were also significantly affected. This was the same age distribution observed by Brazilian researchers in 2016 (Chrcanovic & Gomez, ). Most individuals complain of painless swelling (Buchner et al., ; Resende, Brito, Souza, Gomez, & Mesquita, ), and the clinical appearance of these lesions was variously described as sessile, nodular, smooth‐surfaced, firm, of soft consistency or as a fibrous mass (Buchner et al., ; de Lima, Kitakawa, Almeida, Brandão, & Anbinder, ; Resende et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…Herein, the maxilla was most affected. According to Chrcanovic and Gomez (), the great majority of cases described in the literature appear as isolated case reports or small case series. Buchner et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DGCT is a benign neoplasm of odontogenic epithelium predominantly consisting of ameloblastomatous proliferations. Some tumors have a significant component of basaloid hyperchromatic and isomorphic cells, displayed as sheets . Ghost cells and dentin‐like or osteodentin‐like material can also be found .…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiological study of such lesions is of great importance because provides information that can improve the diagnostic accuracy and will allow pathologists and surgeons to make informed decisions and to refine treatment plans to optimize clinical outcomes (Chrcanovic and Gomez, 2016;2017a;b). The aim of the present study was to integrate the available data published in the literature on SOT and SOT-LPOC into an updated, comprehensive, comparative analysis of their clinical and radiologic features, and to report the frequency of recurrence of these lesions.…”
Section: Introductionmentioning
confidence: 99%